Traditional Medicinal Vegetables in Northern Uganda: An Ethnobotanical Survey - Rebecca Nakaziba; Maxson Kenneth Anyolitho; Sharon Bright Amanya; Crispin Duncan Sesaazi; Frederick Byarugaba; Jasper Ogwal-Okeng; Paul E. Alele (International Journal of Food Science)
Background. A wide range of indigenous vegetables grow in Uganda especially during rainy seasons but scarcely during droughts, except those that are commercially grown. Although a number of these vegetables have medicinal values, they have not been satisfactorily studied besides conservation. Therefore, we conducted a cross-sectional ethnobotanical survey in Northern Uganda in order to document traditional medicinal vegetables and their uses. Methods. Qualitative and quantitative approaches of data collection and analysis were employed using semistructured, interviewer-administered questionnaires as well as key informant interviews following international ethical codes. Fidelity levels and informant consensus factors were also calculated. Results. 13 traditional vegetables belonging to 10 families were reported to serve as folk medicines. The most dominant families were Fabaceae (23.08%) and Solanaceae (15.38%). The most often used vegetables were Corchorus spp., Hibiscus spp., and Asystasiagangeticafor musculoskeletal (51%), gastrointestinal (34.3%), and malaria (31.8%). The vegetables were cultivated in the backyard and the leaves stewed for the different ailments. The informant consensus factor was the highest for Corchorus spp., in the treatment of joint pain/stiffness (0.92-1) while the highest fidelity level was (60.42%) for Amaranthus spp., in the management of anemia. Conclusions. Northern Uganda has numerous traditional vegetables with medicinal benefits. Diseases treated range from gastrointestinal to reproductive through musculoskeletal abnormalities. The community obtains vegetable leaves from the backyard and stews them regularly for the medicinal purposes with no specific dosage. Therefore, we recommend studies to verify in laboratory models the efficacy of these vegetables and standardize the dosages.